America's jails: the search for human dignity in an age of mass incarceration - Jeffreys, Derek S. (Alternative criminology, 2018)
Degradation and disorientation: a glimpse into the Cook County jail -- What is the purpose of a jail? -- A matter of dignity -- Why do we stigmatize inmates? disgust, contempt, and fear in American jails -- What can we do? responding to a crisis -- Conclusion: can we reform the jail? -- Acknowledgments -- Notes -- Bibliography -- Index